IMF and Fragile States : 2018 Evaluation Report. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2018)
This evaluation assesses the IMF's work on countries in fragile and conflict-affected situations (FCS), addressing both (i) its engagement through surveillance, lending, and capacity development and (ii) the frameworks and procedures for its engagement. It finds that the IMF has provided unique and essential services to FCS to restore macroeconomic stability and rebuild core macroeconomic institutions as prerequisites for state building, playing a role in which no other institution can take its place. In this critical role, it is broadly acknowledged to have had a high impact. While the IMF has provided relatively little direct financing, it has catalyzed donor support through its assessment of a country's economic policies and prospects. Notwithstanding this positive assessment, the IMF's overall approach to its FCS work seems to have been conflicted. Not only has it failed consistently to make hard choices necessary to achieve full impact from its engagement in countries where success requires patient and dedicated attention over the long haul, but past efforts have not been sufficiently bold or adequately sustained, and the staff has tended to revert to treating fragile states using IMF-wide norms, rather than as countries needing special attention. The report proposes six recommendations to improve the effectiveness of the IMF's FCS work: (i) to issue a statement of high-level commitment to FCS work for IMFC endorsement; (ii) to create an effective institutional mechanism with the mandate and authority to coordinate and champion such work; (iii) to develop comprehensive strategies for individual FCS; (iv) to adapt its lending toolkit to deliver more sustained financial support to FCS; (v) to take practical steps to increase the impact of its capacity development support to FCS; and (vi) to take steps to incentivize high-quality and experienced staff to work on individual FCS and find pragmatic ways of increasing field presence in high risk locations.